KONTRIBUSI SPIRITUALITAS TERHADAP KEBERMAKNAAN HIDUP MASYARAKAT WARU MALUKU TENGAH YANG MENJALANKAN RITUAL MORI TARI MORI UKNU - Jil Eltha Sopaheluwakan; Arthur Huwae (Sekolah Tinggi Pariwisata Mataram, 2022)
Local culture is a means to apply values that generate strength and hope. This shapes the local community towards a meaningful life goal for the community and the natural surroundings. However, the cultural values that characterize local wisdom are starting to erode, along with the development of science and technology. Therefore, this research aimed to determine the contribution of spirituality toward the meaningful life of the waru community who carry out the mori tari mori uknu ritual. The method used in this research was quantitative with a simple regression design. This research used incidental sampling technique by involving 77 participants at age 18 - 39 years old. The data were collected by using spirituality (questionnaire) scale and meaning in life scale. The result of this research showed that there was a contribution of spirituality toward the meaningfulness of the life of Waru community conduct Mori Tari Mori Uknu ritual (t-test = 11.331 and sig = 0.000) with the contribution of 63,1%.